2018
DOI: 10.1017/s0954579418000639
|View full text |Cite
|
Sign up to set email alerts
|

Major depressive disorder during pregnancy: Psychiatric medications have minimal effects on the fetus and infant yet development is compromised

Abstract: Psychotropic medication use and psychiatric symptoms during pregnancy each are associated with adverse neurodevelopmental outcomes in offspring. Commonly, studies considering medication effects do not adequately assess symptoms, nor evaluate children when the effects are believed to occur, the fetal period. This study examined maternal serotonin reuptake inhibitor and polypharmacy use in relation to serial assessments of five indices of fetal neurobehavior and Bayley Scales of Infant Development at 12 months i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…In women, lower age, a history of cancer, lower alcohol consumption, loneliness and baseline depression symptoms were predictive of depression, but not CRP. As consumption of alcohol is quite widespread in Germany, especially in social contexts, and as the recommended limit (for women) is reached with few drinks, the negative predictive valence of alcohol consumption might have been related to little social contact (and related social drinking) which aggravates the risk for depression 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In women, lower age, a history of cancer, lower alcohol consumption, loneliness and baseline depression symptoms were predictive of depression, but not CRP. As consumption of alcohol is quite widespread in Germany, especially in social contexts, and as the recommended limit (for women) is reached with few drinks, the negative predictive valence of alcohol consumption might have been related to little social contact (and related social drinking) which aggravates the risk for depression 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Fetal movement and heart rate were acquired using a Toitu MT 325 fetal actocardiograph (Toitu Co., Ltd., Tokyo, Japan) via a single transabdominal Doppler transducer, while participants were in a semi‐recumbent position for 20 min (described in previous work Doyle et al., 2015; Gustafsson et al., 2018; Werner et al., 2007)). The fetal data were collected from the Toitu's output port, digitized at 50 Hz using a 16‐bit A/D card (National Instruments 16XE50), and analyzed offline.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that fetuses included in the study were developing typically, we measured their mean heart rate and heart rate variability (standard deviation) as described previously (Doyle et al., 2015; Gustafsson et al., 2018; Werner et al., 2007).…”
Section: Methodsmentioning
confidence: 99%
“…In SRI exposed fetuses, Mulder et al report increased motor activity in the second trimester and increased motor activity during quiet sleep state (i.e., stable fetal HR, low variability) in the third-trimester; however, SRI-treated mothers had comparable psychiatric symptoms to the unmedicated depressed group (28). Gustafsson et al also observed increased motor activity in SRI-exposed fetuses, but only prior to 30-weeks' gestation and found no SRI-related effect on fetal HR, HR variability, or HRmovement coupling (31). Conversely, lower fetal HR variability at 36-weeks' gestation and reduced cerebral blood flow resistance was observed in SRI-exposed fetuses (30), as well as elevated pulmonary blood flow in SRI-exposed fetuses who experienced transient respiratory difficulties at birth (29).…”
Section: Introductionmentioning
confidence: 97%
“…To date, only few studies have investigated whether outcomes of prenatal SRI exposure emerge before birth: during the period of drug exposure. Fetal SRI exposure has been associated with disrupted cardiovascular function (28)(29)(30) and increased fetal motor activity (28,(31)(32)(33); though, findings are not consistent, primarily due to variations in methodology, gestational age and the ability to account for maternal mood. In SRI exposed fetuses, Mulder et al report increased motor activity in the second trimester and increased motor activity during quiet sleep state (i.e., stable fetal HR, low variability) in the third-trimester; however, SRI-treated mothers had comparable psychiatric symptoms to the unmedicated depressed group (28).…”
Section: Introductionmentioning
confidence: 99%